Additional Evidence on the Impact of the International Financial Reporting Standards on Earnings Quality: Evidence from Latin America - Melgarejo, Mauricio (Journal of Applied Business and Economics, 2017)
The purpose of this paper is to explore whether the adoption of the International Financial Reporting Standards (IFRS) has an impact on the quality of earnings in Latin America. Studying a sample of firms from Argentina, Brazil, Chile, Mexico, and Peru, I find that management reports a lower level of discretionary accruals after the implementation of the IFRS. In addition, this study provides evidence that earnings are more persistent and stock prices are more associated with earning numbers after the application of IFRS. This paper provides evidence that earnings quality has increased after the adoption of IFRS in Latin America.